2019
DOI: 10.1186/s12889-019-7278-z
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in breast cancer screening coverage provided under the Brazilian National Health Service between 2008 and 2017

Abstract: Background In Brazil, 70% of the population depends on the public healthcare system. Since early detection is considered crucial, this study aimed to evaluate temporal changes in breast cancer screening coverage provided under the Brazilian National Health Service (SUS) according to the different regions of the country between 2008 and 2017. Methods This ecological study analyzed data on breast cancer screening within the SUS for women aged 50–69 years. Coverage was cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 24 publications
1
9
0
12
Order By: Relevance
“…Concerning the mammography coverage, the year 2019 reflects what happened in the previous years, from 2012 to 2017 9 , when there was no increase in mammography coverage in the female population aged 50 to 69 years who use the SUS services. This probably reflects a political issue, with greater emphasis on the economic and financial situation in which Brazil was immersed in the period under analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the mammography coverage, the year 2019 reflects what happened in the previous years, from 2012 to 2017 9 , when there was no increase in mammography coverage in the female population aged 50 to 69 years who use the SUS services. This probably reflects a political issue, with greater emphasis on the economic and financial situation in which Brazil was immersed in the period under analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study conducted by the Rede Brasileira de Pesquisa em Câncer de Mama [Brazilian Breast Cancer Research Network], following the recommendations of the Brazilian Ministry of Health, according to which women aged between 50 and 69 years must undergo a biennial mammography examination, it was observed that the rate of mammography coverage by the Brazilian Unified Health System (SUS) in this population increased from 14.4% in 2008 to 24.4% in 2012 and, since then, mammography coverage has been stabilized, accounting for 24.2% in 2017 9 .…”
Section: Introductionmentioning
confidence: 99%
“…A broader study by Rodrigues et al evaluated retrospective data regarding mammograms between 2008 and 2016 in the public health system [40]. Around nineteen million mammograms were performed in this period with an increase in coverage of 14.5% annually between 2008 and 2012 followed by a stable period between 2012 and 2017.…”
Section: Current Situation Of Mammographic Screeningmentioning
confidence: 99%
“…1,2 Apesar de uma alta proporção de mulheres afirmarem realizar exames de rastreamento de câncer de colo uterino e de mama, observa-se menor cobertura entre aquelas com maior vulnerabilidade social, principalmente nas regiões mais pobres do país. [3][4][5][6] Este problema parece estar relacionado a dificuldades no acesso a esses exames, [7][8][9][10] além de determinantes sociais, como baixa escolaridade, 4,5,11 raça/cor da pele preta e parda 11,12 e utilização do setor público de saúde. 11 As desigualdades regionais e sociais na cobertura da realização dos exames preventivos de mamografia e citopatológicos tornam-se ainda mais preocupantes diante da constatação de que, no ano de 2020, mais de 80 mil mulheres foram acometidas por câncer de mama ou de colo do útero no Brasil, respectivamente o primeiro e o terceiro tipos de câncer mais frequentes no sexo feminino no país.…”
Section: Introductionunclassified